Copper sulfate acute ecotoxicity and environmental risk for tropical fish - Adilson Ferreira da Silva (Acta Scientiarum. Biological Sciences, 2014)
The aim of this study was to estimate copper sulfate acute toxicity and to determine death percentage and environmental risk on guppy fish ( Phallocerus caudimaculatus ), zebrafish ( Brachydanio rerio ), mato grosso ( Hyphessobrycon eques ), and pacu ( Piaractus mesopotamicus ). Fish were exposed to 0.01, 0.03, 0.05, 0.07, 0.10, and 0.30 mg L -1 (guppy), 0.05, 0.07, 0.10, and 0.30 mg L -1 (zebrafish), 0.07, 0.10, 0.20, and 0.30 mg L -1 (mato grosso) and 9.5, 10.0, 10.5, 11.0, 11.5, and 12.0 mg L -1 (pacu) of copper sulfate, with triplicate control. The estimated 50% average lethal concentr ations (LC50; 96 hours) were 0.05 (guppy), 0.13 (zebrafish); 0.16 (mato grosso) and 10.36 mg L -1 (pacu). Copper sulfate was extremely toxic for guppy, highly toxic for zebrafish and mato grosso and lightly toxic for pacu and presents environmental risk of high adverse effects on the guppy, zebrafish and mato grosso and moderate adverse effect to the pacu. Therefore, the guppy fish, zebrafish, and mato grosso are important alternatives for copper sulfate toxicity evaluation in waterbodies.